SEARCH FOR SOURCE MATERIAL WITH LATE BLIGHT RESISTANCE AMONG POTATO VARIETIES AND CLONES - N. M. Zoteyeva; O. S. Kosareva; Z. Z. Evdokimova (Труды по прикладной ботанике, генетике и селекции)
This paper presents the data obtained during the assessment of potato varieties and breeding clones from the VIR and LENNIISKh (Belogorka) collections for late blight resistance. Tests were performed in the field under heavy infection of Phytophthora infestans (Mont.) de Bary (foliage) and in the laboratory (tubers). Varieties and clones with high and moderate leaf and/or tuber late blight resistance were identified. Leaf and tuber resistance in some varieties depended on the P. infestans population structure and on isolates used for inoculation.